Justice in oral health care : ethical and educational perspectives - Welie, Jos V. M. (Marquette studies in philosophy ;, 2006)
Oral health is an intrinsic part of overall health. The mouth is part of the digestive and respiratory systems; it is essential to spoken communication and facial expression; in fact, toothaches are among the most severe and hence debilitating kinds of pain that a person can suffer. The economic cost of dental disease is staggering, equaling an annual loss of some 20 million days of work in the US alone. But far more disastrous is the personal cost for those suffering from these conditions. More than 100 million US citizens lack dental insurance. There is widespread consensus that the resultin.